1996
DOI: 10.1007/s002340050313
|View full text |Cite
|
Sign up to set email alerts
|

MR signal intensity of the perirolandic cortex in the neonate and infant

Abstract: Our purpose was the study the magnetic resonance (MR) signal intensity of the perirolandic gyri perinatally and to correlate it with the histological findings in formalin-fixed brains, focusing on myelination. MRI of 20 neurologically normal neonates and infants, of 37-64 weeks postconception (PCA), were studied retrospectively. We reviewed four formalin-fixed brains of infants 37-46 weeks PCA microscopically. The posterior cortex of the precentral gyrus (P-PRE) and the anterior cortex of the postcentral gyrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Recent studies suggested that changes in signal intensity from MR imaging might not only refer to myelination but also to the development of nerve cells (e.g. increase in cells) related to these tracts [24]. In our work, however, morphological observation on the neurons and quantitation by PCNA immunocytochemistry (to show dividing cells) on the specimens of different ages did not identify any significant differences in the percentage of dividing new cells between ages in preliminary studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Recent studies suggested that changes in signal intensity from MR imaging might not only refer to myelination but also to the development of nerve cells (e.g. increase in cells) related to these tracts [24]. In our work, however, morphological observation on the neurons and quantitation by PCNA immunocytochemistry (to show dividing cells) on the specimens of different ages did not identify any significant differences in the percentage of dividing new cells between ages in preliminary studies.…”
Section: Discussioncontrasting
confidence: 50%
“…[1][2][3][4][5][6][7]10 These changes are believed to be mainly due to myelination and a decrease in cerebral water content. 11 There are several studies reporting the time course of this signal intensity change in the term or preterm infant or fetus in terms of gestational age at examination, and those studies successfully proved the signal intensity change in most of the structure in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Various processes other than myelination take place within the developing cerebral tissue, including neuronal development, which is associated with the rapid proliferation and formation of oligodendroglial cells, synapses, and dendrites as mentioned above. 5 It also has been suggested that a glutamatergic pathway transiently innervates the globus pallidus during the mammalian perinatal period. 15 This kind of transient innervation may cause synaptic and dendritic formation, resulting in T1 hyperintensity in this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations